DAMPAK LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KEPUASAAN KARYAWAN PERUSAHAAN LOGISTIK - Saifudin, Achmad Budi; Fatihudin, Didin; Mochklas, Mochamad (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.06.TAHUN 2020DO - 10.24843/EEB.2020.v09.i06.p02, 2020)
Knowing and analyzing the impact of the work environment and work motivation on employee job satisfaction in logistics companies is very important. High employee job satisfaction will have an impact on increasing employee productivity and performance. This research method with quantitative, population and sample are employees of logistics company PT. Cipta Krida Bahari. All incoming data are processed using SPSS 20. The results of this study are partially positive and significant work environment and work motivation, and simultaneously work environment and work motivation have a positive and significant effect on employee job satisfaction.